Search for high-mass resonances decaying into ZZ in p(p)over-bar collisions at root s=1.96 TeV - Aaltonen, T; Alvarez Gonzalez, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; et al. (2012)
We search for high-mass resonances decaying into Z boson pairs using data corresponding to 6fb -1 collected by the CDF experiment in pp̄ collisions at √s=1.96TeV. The search is performed in three distinct final states: ZZ→ +-+-, ZZ→ +-νν, and ZZ→ +-jj. For a Randall-Sundrum graviton G *, the 95% CL upper limits on the production cross section times branching ratio to ZZ, σ(pp̄→G *→ZZ), vary between 0.26 pb and 0.045 pb in the mass range 300